Effects of Application of Mycorrhizal Fungi on the Growth and Dry Matter Production of Elephant Grass cv. Mott under Drought Stress - . Syamsuddin; S. Hasan; . Budiman; A. Asrianie (Jurnal Ilmu dan Teknologi Peternakan, 2015)
Research has been conducted to determine the effect of mycorrhizal fungi on growth and dry matter production of elephant grass cv. Mott in drought stress conditions. This study was designed factorially based on completely randomized design consisting of 4 levels of mycorrhizal (0 g, 4 g, 8 g and 12 g), four levels of drought stress (watering every day, every 3 days, every 5 days and every 7 days) and 3 replications for each treatment combination. Based on the statistical analysis and discussion, it can be concluded that the growth and dry matter production elephant grass is strongly influenced by the amount of water available for plants. Giving mycorrhizal up to the level of 12 g does not yet give a significant impact on the growth and production of elephant grass cv. Mott.